2012
DOI: 10.1016/j.ajhg.2011.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in RIPK4 Cause the Autosomal-Recessive Form of Popliteal Pterygium Syndrome

Abstract: The autosomal-recessive form of popliteal pterygium syndrome, also known as Bartsocas-Papas syndrome, is a rare, but frequently lethal disorder characterized by marked popliteal pterygium associated with multiple congenital malformations. Using Affymetrix 250K SNP array genotyping and homozygosity mapping, we mapped this malformation syndrome to chromosomal region 21q22.3. Direct sequencing of RIPK4 (receptor-interacting serine/threonine kinase protein 4) showed a homozygous transversion (c.362T>A) that causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
109
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 54 publications
4
109
0
2
Order By: Relevance
“…This likely explains the intraoral and esophageal fusions and the partial attachment of the limbs to the body wall in RIPK4 − / − mice (Figures 3b, d and f). Similar to the hypoplastic external genitalia observed in humans affected by PPS, 8,9 the genital tubercle was lacking in RIPK4 − / − mice (Figures 3f and 4a). …”
Section: G H and I)supporting
confidence: 67%
See 4 more Smart Citations
“…This likely explains the intraoral and esophageal fusions and the partial attachment of the limbs to the body wall in RIPK4 − / − mice (Figures 3b, d and f). Similar to the hypoplastic external genitalia observed in humans affected by PPS, 8,9 the genital tubercle was lacking in RIPK4 − / − mice (Figures 3f and 4a). …”
Section: G H and I)supporting
confidence: 67%
“…10,11 In addition, IRF6 (interferon regulatory factor 6) and RIPK4 have been implicated in PPS. 8,9,12 We found that similar to IRF6 mutants, 10,11,13 RIPK4 − / − mice 1 have a defective skin barrier function and cleft palate, and RIPK4 − / − keratinocytes fail to differentiate in vitro. In Xenopus, we show that IRF6 controls RIPK4 expression and that RIPK4 can rescue developmental defects imposed by IRF6 dysfunction, thereby identifying a novel genetic interaction between IRF6 and RIPK4.…”
mentioning
confidence: 79%
See 3 more Smart Citations